Sexual Violence And Its Relationship With Human Trafficking And The Provisions Of Commercial Law - Nomensen Freddy Siahaan; Agustina Wati (Journal of Social Research, 2024)
This research discusses the phenomenon of sexual violence related to the practice of human trafficking and how the provisions of commercial law play a role in this context. Sexual violence is often part of the exploitation experienced by victims of human trafficking, where women and children are the most vulnerable groups. This study highlights how trade law regulations, both national and international, can affect human trafficking practices and efforts to prevent and enforce sexual violence. This analysis involves a multidisciplinary approach, combining legal, social, and economic aspects to provide a comprehensive understanding of the relationship between sexual violence, human trafficking, and commercial law. The results of this study are expected to contribute to the development of more effective policies in preventing and tackling human trafficking and protecting victims of sexual violence.